Pengaruh Model PBL Terhadap Hasil Belajar dan Motivasi Belajar Siswa - Rohmah Putri, Maulidatur; Rodliyah, Iesyah (Universitas Islam Jember, 2024)
This study aims to describe the effect of the PBL model on learning outcomes and student motivation in the flat-sided geometric material at SMPN 1 Jogoroto. Two classes of class VIII students were randomly selected to be divided into an experimental group and a control group to serve as research samples. The instruments used were tests and questionnaires. Inferential analysis will be used to test the data obtained from the control and experimental classes. The results showed that there was no significant effect of the PBL model on the learning outcomes and motivation of students at SMPN 1 Jogoroto in terms of gender, with the average learning outcomes and learning motivation of the experimental class students being higher than that of the control class students, both boys, and girls. This means that there is an influence of the PBL model on learning outcomes and student motivation. Keywords: PBL, learning outcomes, learning motivation